2021
DOI: 10.1038/s41598-021-00913-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of type of reconstructed residence on social participation and mental health of population displaced by disasters

Abstract: After disasters, people are often forced to reconstruct or move to new residences. This study aimed to reveal the association between the types of reconstructed residences and psychosocial or psychiatric conditions among the population. A total of 1071 adult residents in a coastal town, whose houses were destroyed by the tsunami caused by the Great East Japan Earthquake, enrolled in the study five years after the disaster. The type of reconstructed post-disaster residences (reconstructed on the same site/disas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The studies suggested associations between psychological distress and physical conditions among residents affected by the disaster 47–49 . Like other affected areas, living conditions, 43,50,51 employment status, 46 daily walking habit 45 and social capital 44 were associated with the mental health of the affected community.…”
Section: Advances In Mental Health Disaster Response After the Gejementioning
confidence: 99%
“…The studies suggested associations between psychological distress and physical conditions among residents affected by the disaster 47–49 . Like other affected areas, living conditions, 43,50,51 employment status, 46 daily walking habit 45 and social capital 44 were associated with the mental health of the affected community.…”
Section: Advances In Mental Health Disaster Response After the Gejementioning
confidence: 99%
“…During disasters, people may evacuate to escape life-threatening circumstances. Persons severely impacted by disasters who fail to evacuate may incur physical health issues as well as long-term mental health problems 11 – 13 . Houses damaged by the disaster may need repair before they are again inhabitable, forcing residents to relocate until their homes are inhabitable.…”
Section: Introductionmentioning
confidence: 99%
“…During disasters, people may evacuate to escape life-threatening circumstances. Persons severely impacted by disasters who fail to evacuate may incur physical health issues as well as long-term mental health problems (Few, 2013;Lane et al, 2013;Suzuki et al, 2021). Houses damaged by the disaster may need repair before they are again inhabitable, forcing residents to relocate until their homes are inhabitable.…”
Section: Introductionmentioning
confidence: 99%